Willingness and Perception About COVID-19 Vaccine Among Rural Adults (Journal of Rangpur Medical College, 2023)
Introduction: The most successful and cost-effective method of preventing the spread of COVID-19 infection is vaccination. But there are challenges to vaccinating the mass population in a developing country like Bangladesh. This survey aimed to assess the willingness to receive and perception of COVID-19 vaccines and the association of this willingness with the baseline characteristics and the level of perception of the respondents.Method: This cross-sectional study was conducted among 672 rural people from six villages of Palashbari Upazilla, Gaibabdha district. A convenient sampling technique was used and data were collected by face-to-face interview.Result: Almost two third of the respondents of this study were _30 years old and the average age of respondents was 37.43±17.13 years. Majorities of the respondents were female (54.6%). About 89.1% of the respondents in this study were willing to be vaccinated and the main reason for this willingness includes respondents’ belief about the vaccine protection against COVID-19 (91.8%) reduced the fear of the respondents (60.6%), government suggestion (45.1%). The main reasons behind unwillingness included fear of side effects (71.8%), doubt about vaccine safety and efficacy (46.5%), and ignorance (59.2%). Regarding perception about the COVID-19 vaccine, more than half of the respondents (51.2%) had good perception whereas 29.8% had average perception and 19.0% of respondents had poor perception. In this study, females were significantly more willing to be vaccinated than male respondents (p=0.027). Respondents age group